Long-Run Price Elasticities of Demand for Credit: Evidence from a Countrywide Field Experiment in Mexico - Karlan, Dean; Zinman, Jonathan (Review of Economic Studies, 2019)
Abstract We use randomized interest rates, offered across eighty geographically distinct regions for twenty-nine months by Mexico’s largest microlender, to sketch the adjustment from a price change to a new equilibrium. Demand is elastic, and more so over the longer run; e.g. the dollars-borrowed elasticity increases from -1.1 in Year one to -2.9 in Year three. Credit bureau data do not show evidence of crowd-out, although this and other null results are imprecisely estimated. The lender’s profits increase, albeit noisily, starting in Year two. But competitors do not respond by reducing rates. These findings, together with other results, suggest that informational frictions are important, and that cutting rates furthered Compartamos Banco’s “double bottom line” of improving social welfare subject to a profitability constraint.